Oxidative stress and detoxification biomarker responses in aquatic freshwater vertebrates exposed to microcystins and cyanobacterial biomass - Paskerová, Hana; Hilscherová, Klára; Bláha, Luděk (Environmental science and pollution research international, 2012)
Cyanobacterial blooms represent a serious threat to the aquatic environment. Among other effects, biochemical markers have been studied in aquatic vertebrates after exposures to toxic cyanobacteria. Some parameters such as protein phosphatases may serve as selective markers of exposure to microcystins, but under natural conditions, fish are exposed to complex mixtures, which affect the overall biomarker response. This review aims to provide a critical summary of biomarker responses in aquatic vertebrates (mostly fish) to toxic cyanobacteria with a special focus on detoxification and oxidative stress. Detoxification biomarkers such as glutathione (GSH) and glutathione-S-transferase (GST) showed very high variability with poor general trends. Often, stimulations and/or inhibitions and/or no effects at GSH or GST have been reported, even within a single study, depending on many variables, including time, dose, tissue, species, etc. Most of the oxidative stress biomarkers (e.g., superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase) provided more consistent responses, but only lipid peroxidation (LPO) seemed to fulfill the criteria needed for biomarkers, i.e., a sufficiently long half-life and systematic response. Indeed, reviewed papers demonstrated that toxic cyanobacteria systematically elevate levels of LPO, which indicates the important role of oxidative damage in cyanobacterial toxicity. In summary, the measurement of biochemical changes under laboratory conditions may provide information on the mode of toxic action. However, comparison of different studies is very difficult, and the practical use of detoxification or oxidative stress biomarkers as diagnostic tools or early warnings of cyanobacterial toxicity is questionable.
Keywords: sinice; Glutathione; škodlivý vodní květ; glutathiontransferasa; Cyanobacteria; Oxidative Stress; Harmful Algal Bloom; Lipid Peroxidation; Glutathione Transferase; zvířata; Microcystins; glutathion; biologické markery; mikrocystiny; Fishes; oxidační stres; Biomarkers; ryby; Biomass; peroxidace lipidů; biomasa; Animals